Effect of anode iridium oxide content on the electrochemical performance and resistance to cell reversal potential of polymer electrolyte membrane fuel cells. (19th April 2021) - Ahn, Chi-Yeong; Kang, Sun Young; Choi, Hyuck Jae; Kim, Ok-Hee; Sung, Yung-Eun; Cho, Yong-Hun
Abstract: An ideal polymer electrolyte membrane fuel cell (PEMFC) is one that continuously generates electricity as long as hydrogen and oxygen (or air) are supplied to its anode and cathode, respectively. However, internal and/or external conditions could bring about the degradation of its electrodes, which are composed of nanoparticle catalysts. Particularly, when the hydrogen supply to the anode is disrupted, a reverse voltage is generated. This phenomenon, which seriously degrades the anode catalyst, is referred to as cell reversal. To prevent its occurrence, iridium oxide (IrO2 ) particles were added to the anode in the membrane-electrode assembly of the PEMFC single-cells. After 100 cell reversal cycles, the single-cell voltage profiles of the anode with Pt/C only and the anodes with Pt/C and various IrO2 contents were obtained. Additionally, the cell reversal-induced degradation phenomenon was also confirmed electrochemically and physically, and the use of anodes with various IrO2 contents was also discussed. Graphical abstract: Image 1 Highlights: The addition of IrO2 particles to the anode in the PEMFC is proposed. All the MEAs with IrO2 exhibited stable profiles after the cell reversal (CR) tests. In the CR condition, IrO2 efficiently prevented corrosion of carbon in Pt/C. This study demonstrates enhanced durability in CR environment by inducing IrO2 .